2002
DOI: 10.1016/s0924-9338(02)00678-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Alzheimer’s disease: is there a temporal relationship between the onset of depression and the onset of dementia?

Abstract: Alzheimer's disease (AD) patients often present with concurrent major depression (MD). To investigate the reasons for this comorbidity, e.g. MD being a risk factor for AD, or both diagnoses having a common neurobiology, the temporal relationship between the first onset of AD and of MD during lifetime was investigated-57 out of 146 AD patients had a lifetime diagnosis of MD. The correlation between the ages at onset of MD and dementia was calculated. The incidence of MD in AD patients in several 5-year-interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 28 publications
0
29
0
8
Order By: Relevance
“…22 It has been suggested that the increased incidence of depression in patients with AD points to a common neurobiological basis for both diseases. 23 An important finding in our work is that most patients with MCI and depression responded poorly to antidepressants and developed dementia; this may help to individualize the risk of dementia more accurately. A cohort of 112 patients with MCI was followed up for 3 years, and depression at baseline was associated with conversion to AD but not with a more rapid cognitive decline.…”
Section: Commentmentioning
confidence: 78%
“…22 It has been suggested that the increased incidence of depression in patients with AD points to a common neurobiological basis for both diseases. 23 An important finding in our work is that most patients with MCI and depression responded poorly to antidepressants and developed dementia; this may help to individualize the risk of dementia more accurately. A cohort of 112 patients with MCI was followed up for 3 years, and depression at baseline was associated with conversion to AD but not with a more rapid cognitive decline.…”
Section: Commentmentioning
confidence: 78%
“…It is widely known that depression and dementia oftentimes co-exist (Heun, Kockler, & Ptok, 2002;Heun, Kockler, & Ptok, 2003). Depression is the most prevalent mental disorder in the U.S. population (Robins & Regier, 1991) and is the most widely studied psychiatric outcome in the caregiving literature (Clyburn, Stones, Hadjistavropoulos, & Tuokko, 2000;Yee & Schulz, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, the deleterious effects of dementia have been well-established. Persons with dementia or Alzheimer's disease (AD) Correspondence (Heun et al, 2002;Heun et al, 2003), higher rates of disability (Schulz et al, 2002;Thomas, 2001), and a number of other behavioral disturbances (McCann, Gilley, Bienias, Beckett, & Evans, 2004). Furthermore, there is ample evidence that caregivers to individuals with cognitive impairment, specifically dementia, experience a host of deleterious outcomes (Dura, Stukenberg, & Kiecolt-Glaser, 1991;Grant et al, 2002;Moritz, Kasl, & Ostfeld, 1992;Schulz, Visintainer, & Williamson, 1990;Schulz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggest that common risk factors, particularly cerebrovascular pathology or a common underlying neurobiological process for depression and cognitive decline or dementia may explain this. [14][15][16][17][18] The vascular depression hypothesis has been invoked to explain the observed sex difference in risk of cognitive decline or dementia after depression. The limited data from a recent study 11 support the suggestion that depression in older men might reflect a form of vascular depression associated with cerebral vascular pathology or multi-infarct disease that may amplify the process of dementia or cognitive decline and accelerate the onset of dementia symptoms.…”
mentioning
confidence: 99%